Nursing UCLA, 40 Promotions of efforts and illusions (Revista Venezolana de Salud Pública, 2018)
The history of Nursing in the state of Lara, Venezuela, begins at the Hospital "La Caridad", created in 1918 (now the Museum of Barquisimeto), where the Sisters of Charity (Sisters of St. Joseph of Tarbes) arrived from France. which were requested by Dr. Luis Razetti, to become the First Nurses of Lara State, it would take many decades for the Nursing Program in the Deanship of Medicine to be created due to the importance in the promotion of health in the region. of the Centroccidental University "Lisandro Alvarado", UCLA, in the month of October 1994 (in 2019 it is 25 years old) after being approved by the National Council of Universities (CNU) in January of this same year, with which the Deanery expanded its academic capacity, so, in 2008, it was renamed the Deanship of Health Sciences (CNU of 11/22/2007), graduating between 1994 and 2019, forty Promotions of Higher Technicians Univers In Nursing, from here, we have, that the first promotion of Nursing Technicians of UCLA, graduated on November 26, 1998 (Figure 1), choosing as eponymous Dr. Maria Gomez (first Director of the Nursing Program being the Sponsors of this nascent Promotion, Dr. Aida Torres, Lcda. Noris Zambrano, Lcda. Dilia Bohórquez and Dr. Oswaldo Valdivia2,3, 25 years after the XL Promotion of TSU in Nursing UCLA (Figure 2), is sponsored by Dr. Milva Javitt, MSc. Ma Laura Lorenzo, Dr. Migdalis Giménez, Lcda. Dairi Díaz and Lcdo. Anyer Heredia
Keywords: UCLA; nursing; technicians